Nest position and reed density influence nest defence behaviour of Great Reed Warbler. Issue 1 (2nd January 2017) - Mérő, T.O.; Žuljević, A.
Abstract : Knowledge of the effects of nest position with regards to distance from shore and vegetation structure on the nest defence behaviour of Great Reed Warblers is lacking. Nest defence behaviour was investigated in the case of 110 monogamous breeding pairs during the breeding season of 2011. We found that nest distance from shoreline and from the reed edge adjacent to water, and reed density, influenced nest defence behaviour positively. However, time elapsed since hatching did not affect parental behaviour. Similar to what was found in previous studies, females defended nests more intensively. Previous papers reported higher predation pressure near both reed edge types (near shoreline and water) than in interior parts of the reed bed, and considering these and our results we suggest that the nest defence pattern of monogamous Great Reed Warblers may vary similarly near both edge types, while in the case of interior parts of reed beds further studies are required for proper conclusions.